2017
DOI: 10.15406/mojgg.2017.01.00013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Burn Injury and Factors in Relation to Infection among Pediatric Patients

Abstract: Burn injury is one of the most common and devastating forms of trauma and a major health problem of pediatric morbidity and mortality worldwide. The risk of infection in pediatric burns is well-known. An observational checklist was used by the researcher to assess the patients' characteristics and factors related to burn injury and infection from 1037 pediatric patients. The observational data collection showed that 56.5% of patients were males. The highest risk groups for burn injury are preschool stages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
6
10
0
Order By: Relevance
“…But many studies noted more incidence in male or equal incidence [1,2,4,5,6,8] in this region of Indian pupils give less importance to female as compared to male so level of care and observation get low in female that may be the cause of high incidence in female In our study, scalds were the main cause of burn in the majority of patients, similar to other studies. [1,2,4,5,6,7,8,9] Flame burn is the second most common cause of pediatric burn injury. Flame burns are generally caused by chimni (homemade lamp,), choola and other open fires.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…But many studies noted more incidence in male or equal incidence [1,2,4,5,6,8] in this region of Indian pupils give less importance to female as compared to male so level of care and observation get low in female that may be the cause of high incidence in female In our study, scalds were the main cause of burn in the majority of patients, similar to other studies. [1,2,4,5,6,7,8,9] Flame burn is the second most common cause of pediatric burn injury. Flame burns are generally caused by chimni (homemade lamp,), choola and other open fires.…”
Section: Discussionsupporting
confidence: 87%
“…In our study 40.31%children were up to 5 years of age some other studies also noted same in their studies [1,4,5,6,7,8] . The higher incidence in this age group is due to the curious nature of infants and toddlers and the urge to mostly pull and push things around.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study is similar to other previous studies. 13,31,[33][34][35][36] This can be explained by the mechanism of injury: when someone contacts with hot or boiling water, hot tea, chemical, electrical, and radiation, patients may present with different burned anatomic sites, in which extremities are common due to manipulation of different objects.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iraq among pediatric burn patients reported a significant relationship between wound infection and death in 37.7% of the deaths recorded. The deaths were attributed to inappropriate antibiotic use due to delays in laboratory testing including wound swab and blood culture that might have resulted in septicemia and eventually death [ 6 ]. In studies involving pediatric patients, sepsis was found to be the leading cause of death in Mozambique (100%) and the second cause of death in Cameroon (24%) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%